2
$\begingroup$

I've run across several integral representations of $H_z$ such as the following (see Harmonic Number Integral Representations).

(1) $\quad H_z=\int\limits_0^1 \frac{1-t^z}{1-t} \, dt\,,\qquad\qquad\qquad\qquad\Re(z)>-1$

(2) $\quad H_z=\int\limits_0^\infty\left(\frac{e^{-t}}{t}-\frac{(t+1)^{-z-1}}{t}\right)\,dt+\gamma\,,\quad\Re(z)>-1$

(3) $\quad H_z=\int\limits_0^\infty\frac{e^{-t}-e^{-(z+1)\,t}}{1-e^{-t}}\,dt\,,\quad\qquad\qquad\quad\Re(z)>-1$

(4) $\quad H_z=\int\limits_0^1\left(\frac{t^z}{t-1}-\frac{1}{\log (t)}\right)\,dt+\gamma\,,\quad\quad\Re(z)>-1$


I believe the following integral representation of $H_z$ is also valid but can't seem to translate it to any of the integral representations illustrated in (1) to (4) above.

(5) $\quad H_z=-(z+1)\int\limits_0^\infty\frac{\log(t)}{(t+1)^{z+2}}\,dt\,,\qquad\quad\Re(z)>-1$


The digamma function $\psi(z)$ defined in (6) below is related to $H_z$ as illustrated in (7) below.

(6) $\quad\psi(z)=\frac{\partial\,\log(\Gamma(z))}{\partial\,z}=\frac{\Gamma'(z)}{\Gamma(z)}$

(7) $\quad H_z=\psi(z+1)+\gamma$


The integral representations of $\psi(z)$ illustrated in (8) to (12) below (see PolyGamma Integral Representations) are related to the integral representations of $H_z$ illustrated in (1) to (4) above.

(8) $\quad\psi(z)=\int\limits_0^1\frac{1-t^{z-1}}{1-t}\,dt-\gamma\,,\qquad\quad\Re(z)>0$

(9) $\quad\psi(z)=\int\limits_0^\infty\left(\frac{e^{-t}}{t}-\frac{(t+1)^{-z}}{t}\right)\,dt\,,\quad\Re(z)>0$

(10) $\quad\psi(z)=\int\limits_0^\infty\frac{e^{-t}-e^{-z\,t}}{1-e^{-t}}\,dt-\gamma\,,\qquad\Re(z)>0$

(11) $\quad\psi(z)=\int\limits_0^1\left(\frac{t^{z-1}}{t-1}-\frac{1}{\log (t)}\right)\,dt\,,\quad\Re(z)>0$


The following integral representation of $\psi(z)$ follows from (5) and (7) above but again I can't seem to translate it to any of the integral representations illustrated in (8) to (11) above.

(12) $\quad\psi(z)=-z\int_0^\infty\frac{\log(t)}{(t+1)^{z+1}}\,dt-\gamma\,,\quad \Re(z)>0$


Question: What is the proof of the integral representations of $H_z$ and $\psi(z)$ illustrated in (5) and (12) above?

$\endgroup$
1
$\begingroup$

For $z \in \mathbb{C}$ with $\Re (z) > -1$ let $f(z) = (z+1) \int_0^\infty \frac{-\log(t)}{(1+t)^{z+2}} \, \mathrm{d} t$. Then $f(0) = 0$, so $$ f(z) = f(z) - f(0) = \int \limits_0^\infty (-\log(t)) \left[\frac{z+1}{(1+t)^{z+2}} - \frac{1}{(1+t)^2}\right] \, \mathrm{d} t \, .$$ Now we can integrate by parts and let $s = \frac{1}{1+t}$ to find $$ f(z) = \int \limits_0^\infty \frac{1}{t(1+t)} \left[1 - \frac{1}{(1+t)^z}\right] \, \mathrm{d} z = \int \limits_0^1 \frac{s}{\frac{1}{s} - 1} (1 - s^z) \, \frac{\mathrm{d} s}{s^2} = \int \limits_0^1 \frac{1 - s^z}{1-s} \, \mathrm{d} s = H_z$$ from your first identity.

Alternatively, we can prove the desired result directly using differentiation under the integral sign: \begin{align} f(z) &= - (z+1) \frac{\mathrm{d}}{\mathrm{d} u} \int \limits_0^\infty \frac{t^{u-1}}{(1+t)^{z+2}} \, \mathrm{d} t \, \Bigg\vert_{u=1} \stackrel{(1+t)^{-1} = s}{=} - (z+1) \frac{\mathrm{d}}{\mathrm{d} u} \int \limits_0^1 s^{z+1-u} (1-s)^{u-1} \, \mathrm{d} s \, \Bigg\vert_{u=1}\\ &= - (z+1) \frac{\mathrm{d}}{\mathrm{d} u} \frac{\Gamma(z+2-u)\Gamma(u)}{\Gamma(z+2)} \, \Bigg\vert_{u=1} = \frac{(z+1)\Gamma(z+1) \Gamma(1)}{\Gamma(z+2)} [\psi (z+1) - \psi(1)] \\ &= \psi(z+1) + \gamma = H_z \, . \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.